Experimental Analysis of Gas Split Injection Effect on Dual-Fuel Engine Performance - Semin; Yudha Prasetiyo; Beny Cahyono; Frengki Mohamad Felayati (International Journal of Marine Engineering Innovation and Research, 2021)
The application of a dual-fuel engine has massively been used as the main engine. However, in dual-fuel engine operations, problems occur in low-load operations. The combustion quality with unstable combustion conditions and relatively low thermal efficiency. In this research, a gas split injection strategy was implemented on the dual-fuel engine. The purpose of this research is to compare the performance of the engine between dual-fuel operations using gas split injection strategy and single injection. Furthermore, split injection is a fuel injection system by dividing the injection into several injection stages with a certain mass and period. This injection system was applied on a dual-fuel engine system, which was previously a modification of the conventional diesel Yanmar TF 85 MH. The variation in this study is the injection split ratio (ISR) 75-25, variations in injection time, and variations in load with specified engine speed at 2000 RPM. The results obtained in this study are the best variations found in ISR 75-25 gas split injection with injection distance at 260°bTDC & 244°bTDC. Due to the injection distance, a significant difference occurred in all parameters tested between single injection and split injection. The significance of the difference in power, torque, BMEP, SFOC, and the thermal efficiency only occurs at 100% load, which is 4.3%; 4.2%; 4.2%; 16%; 18.3%.